From Urban Vulnerabilities to Resilience: Lessons from Messina's Integrated Risk Approach - Giovanna Ferramosca; Anna Terracciano (Alanya Üniversitesi, 2023)
In the city of Messina, the multiplicity of vulnerable situations is a distinctive feature and is representative of the pervasiveness of the risk conditions present in the Italian territory. The critical residential tissues are part of an extended geography in which, to the conditions of seismic and hydro geomorphological vulnerability, are added additional criticalities including altered natural resources, abandoned infrastructure, brownfields, quarries, and unregulated landfills, etc. Despite this, for Messina, there is still no urban planning tool capable of interpreting in an integrated way the risks present, which instead continue to be addressed on an emergency basis and individually, without considering the interactions that are generated and of further damage. For these reasons, Messina was chosen as a prototypical case study, at the national level, to start an experimentation aimed at developing an urban planning tool capable of a new integrated approach to risk interpretation and management. In this process, a decisive role was aimed at building an updated knowledge of the territory through the identification of widespread critical conditions using multiple GIS tools and thanks to the interaction of some analytical-specialist readings from different sources. The results of this process are represented in a system of maps that are strongly integrated with each other and constitute a working document for the interdisciplinary group drafting the General Urban Plan.